Duodenum-preserving pancreatic head resection compared to pancreaticoduodenectomy: A systematic review and network meta-analysis of surgical outcomes - Guo, Shixiang; Zhou, Qiang; Yang, Jiali; Tao, Junyu; Zhang, Junfeng; Wang, Huaizhi (Frontiers in Surgery, 2023)
Objectives: In this systemic review and network meta-analysis, we investigated pancreaticoduodenectomy (PD), pylorus-preserving pancreaticoduodenectomy (PPPD) and different modifications of duodenum-preserving pancreatic head resection (DPPHR) to evaluate the efficacy of different surgical procedures. Methods: A systemic search of six databases was conducted to identify studies comparing PD, PPPD and DPPHR for the treatment of pancreatic head benign and low-grade malignant lesions. Meta- and network meta- analyses were performed to compare different surgical procedures. Results: 44 studies were enrolled in the final synthesis. Three categories of total 29 indexes were investigated. DPPHR group had better working ability, physical status, weight gain and less postoperative discomforts than whipple group, while both groups had no differences in quality of life (QoL), pain scale scores and other 11 indexes. Network meta-analysis of single procedure found DPPHR had a larger probability of best performance in 6 of 8 analyzed indexes than PD or PPPD. Conclusion: DPPHR and PD/PPPD have equal effect to improve QoL and pain relief, while PD/PPPD has more severe symptom and more complications after surgery. PD, PPPD and DPPHR procedures have different strength in the treatment of pancreatic head benign and low-grade malignant lesions.